Enhancing Early Childhood Educators’ Learning Media Design Skills through Canva-Based Training: Evidence from Indonesian Preschool Settings - Indah Widya Ningrum; Laily Nur Aisiyah (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2026)
Background of the study: Digital learning media competencies have become increasingly important for early childhood educators in creating engaging and interactive learning environments. However, many preschool educators still experience limitations in designing visually appealing and pedagogically appropriate instructional media. Canva-based training has emerged as a practical strategy to strengthen educators’ digital media design competencies, particularly in early childhood education settings with limited technological resources. Aims and scope of paper: This study aimed to examine the effect of Canva-based learning media training on the learning media design skills of educators at Nuris Playgroup and Bina Anaprasa Nuris Kindergarten, Jember, Indonesia. Methods: This study employed a pre-experimental method using a one-group pretest–posttest design. The participants consisted of 14 educators, including three educators from Nuris Playgroup and eleven educators from Bina Anaprasa Nuris Kindergarten. Data were collected through pretest and posttest assessments of educators’ learning media design skills following the implementation of Canva training. Data analysis was conducted using the Wilcoxon Signed-Rank Test with SPSS version 27 to determine the significance of changes before and after the intervention. Results: The findings revealed a significant improvement in educators’ learning media design skills after participating in the Canva-based training program. The Wilcoxon Signed-Rank Test showed a significance value of 0.001, which was lower than the threshold of 0.05, indicating that the intervention had a statistically significant positive effect on educators’ competencies in designing digital learning media. The training also enhanced educators’ creativity, confidence, and ability to develop more visually engaging instructional materials for early childhood learning activities. Contribution: This study contributes to the growing literature on digital competency development in early childhood education by demonstrating the effectiveness of Canva-based training in improving educators’ instructional media design skills. The findings highlight the potential of accessible digital platforms to support teacher professional development and promote more innovative and interactive learning experiences in preschool education contexts.